“ADVANCES IN PEPTIDE- AND ANTIBODY-TARGETED NANOCARRIERS FOR CANCER THERAPY AND IMAGING” - Raj V. Pachani; Tapaskumar M. Shah; Dhruv Soni (Journal of Population Therapeutics and Clinical Pharmacology, 2021)
Using nanocarriers to deliver drugs directly to cancer cells is a new and effective approach that helps make treatments work better and causes less harm to healthy tissues. Specific peptides and special types of antibodies, called scFvs, are chosen through methods like in vivo and in vitro phage display. This help target only the receptors found on cancer cells. Nanocarriers, such as liposomes, polymeric nanoparticles, and mesoporous silica nanoparticles (MSNPs), are simple platforms that help carry the drugs to the right place as well as complex constructs like protocells, enable precise delivery of chemotherapeutics, imaging agents, and theranostic cargos. Surface functionalization of nanocarriers with targeting moieties through direct or multi-step conjugation strategies further enhances tumor accumulation, cellular uptake, and therapeutic outcomes while preserving ligand functionality. Advances in biocompatible, biodegradable, and high-capacity nanocarriers combined with optimized conjugation techniques hold significant potential for personalized cancer therapy and image-guided treatment.